2021
DOI: 10.1007/s00253-021-11642-y
|View full text |Cite
|
Sign up to set email alerts
|

Upstream process optimization and micro- and macrocarrier screening for large-scale production of the oncolytic H-1 protoparvovirus

Abstract: The oncolytic virus H-1PV is a promising candidate for various cancer treatments. Therefore, production process needs to be optimized and scaled up for future market release. Currently, the virus is produced with minimum essential medium in 10-layer CellSTACK® chambers with limited scalability, requiring a minimum seeding density of 7.9E3 cells/cm2. Production also requires a 5% fetal bovine serum (FBS) supplementation and has a virus yield up to 3.1E7 plaque-forming units (PFU)/cm2. Using the animal-free cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In this study, it was demonstrated that a seeding density of 5 × 10 3 cells/cm 2 led to the highest functional LVV titers at small scale when compared with 7 × 10 3 or 2.5 × 10 4 cells/cm 2 . This low seeding density was recently used in the iCELLis Nano bioreactor to generate oncolytic H-1 protoparvovirus for cancer treatments, 32 but was never previously used for LVV production in which the lowest seeding density published was 7 × 10 3 cells/cm 2 . 25 The reduction in the inoculation cell density resulted in a delay in transfection from 48 to 120 h, but we considered that an overall process of 7 days is an acceptable process length for the production of these viral vectors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was demonstrated that a seeding density of 5 × 10 3 cells/cm 2 led to the highest functional LVV titers at small scale when compared with 7 × 10 3 or 2.5 × 10 4 cells/cm 2 . This low seeding density was recently used in the iCELLis Nano bioreactor to generate oncolytic H-1 protoparvovirus for cancer treatments, 32 but was never previously used for LVV production in which the lowest seeding density published was 7 × 10 3 cells/cm 2 . 25 The reduction in the inoculation cell density resulted in a delay in transfection from 48 to 120 h, but we considered that an overall process of 7 days is an acceptable process length for the production of these viral vectors.…”
Section: Discussionmentioning
confidence: 99%